2018
DOI: 10.1007/s00247-018-4216-7
|View full text |Cite|
|
Sign up to set email alerts
|

Inter- and intra-observer reliability of contrast-enhanced magnetic resonance imaging parameters in children with suspected juvenile idiopathic arthritis of the hip

Abstract: There were large differences across variables and only moderate agreement between observers. The most reliable parameters were presence of joint effusion and bone marrow oedema and subjective assessment of synovium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Imaging is regularly used as a diagnostic adjunct in JIA to support clinical evaluation [ 25 ]. Plain radiographs have previously been the traditional first-line imaging of choice.…”
Section: Diagnosis Of Jiamentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging is regularly used as a diagnostic adjunct in JIA to support clinical evaluation [ 25 ]. Plain radiographs have previously been the traditional first-line imaging of choice.…”
Section: Diagnosis Of Jiamentioning
confidence: 99%
“…Plain radiographs have previously been the traditional first-line imaging of choice. However, increasingly more varied imaging techniques are being employed to detect active inflammation such as musculoskeletal ultrasonography and contrast enhanced magnetic resonance imaging (MRI) [ 25 ]. These imaging tools contribute greater diagnostic value than plain radiograph imaging, but they are relatively expensive and remain less accessible than is needed for routine use in the outpatient clinic setting.…”
Section: Diagnosis Of Jiamentioning
confidence: 99%
“…Currently, a validated MRI scoring system for the hips has not been established (Table 2 ). Porter-Young et al [ 85 ] have shown the most reliable MRI parameters on which a scoring system might be based.
Fig.
…”
Section: Paediatric-specific Items Per Jointmentioning
confidence: 99%
“…For children, however, although several scoring systems have been proposed [ 12 16 ], no child- and hip-specific scoring system including both inflammatory and permanent changes has been validated [ 17 ]. In one study including 79 children with hip involvement, of whom 22 had confirmed JIA, the inter- and intraobserver agreement of several selected parameters were addressed using a simplified MR-based scoring system on a 0–1 scale [ 14 ]. The most reliable features were the presence of joint effusion, bone marrow edema and the subjective assessment of synovium [ 14 ].…”
Section: Introductionmentioning
confidence: 99%